PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON INVESTOR DALAM SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI DI INDONESIA - Elsa, Ongkowijoyo (Business Accounting Review, 2015)
The effect of corporate social responsibility on investor response had been studied before. However, there was a mix finding of those researches and none of them had been done in Infrastructure, Utility, and Transportation Sector in Indonesia. The aim of this research was to examine the effect of corporate social responsibility on investor response in Infrastructure, Utility, and Transportation sector in Indonesia.CSR was measured by GRI Index version 3.1 while investor response was measured by cumulative abnormal return. The control variables used in this research were return on assets (ROA), firm size, debt-to-equity ratio (DER), and market share. 136 firm years during 2008-2012 were used as a sample and analyzed using multiple regression analysis method.The results indicated that CSR and the control variables of ROA and firm size had no influence on investor response. On the other hand, DER had negative influence and market share had positive influence toward investor response.